2018
DOI: 10.1371/journal.pone.0195788
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between genetic variation and cellular environment in skeletal muscle gene expression

Abstract: From whole organisms to individual cells, responses to environmental conditions are influenced by genetic makeup, where the effect of genetic variation on a trait depends on the environmental context. RNA-sequencing quantifies gene expression as a molecular trait, and is capable of capturing both genetic and environmental effects. In this study, we explore opportunities of using allele-specific expression (ASE) to discover cis-acting genotype-environment interactions (GxE)—genetic effects on gene expression th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…While GxE interactions on human phenotype have been difficult to assess, GxE interactions in relation to gene expression have been studied under various contexts [8,[12][13][14][15][63][64][65]. Overlapping these effects with TF-eQTLs as in our analysis, or even performing TF-eQTL analysis in the environmental exposure datasets themselves, provides mechanistic hypotheses of how environmental effects impact genetic control of gene expression and phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…While GxE interactions on human phenotype have been difficult to assess, GxE interactions in relation to gene expression have been studied under various contexts [8,[12][13][14][15][63][64][65]. Overlapping these effects with TF-eQTLs as in our analysis, or even performing TF-eQTL analysis in the environmental exposure datasets themselves, provides mechanistic hypotheses of how environmental effects impact genetic control of gene expression and phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Response QTL mapping studies not only uncovered context-specific functional genetic variants, but also uncovered the importance of personalized genomic characterizations in the study of environmental risk for human health (e.g. (Moyerbrailean et al, 2016; Mangravite et al, 2013; Knowles et al, 2018; Taylor et al, 2018; Knowles et al, 2017; Nedelec et al, 2016; Barreiro et al, 2011; Maranville et al, 2011)). Overall, our understanding of the role of genetic variation in modulating the RNA-processing response to environmental perturbations is still quite limited.…”
Section: Genetic Regulation Of Rna Processingmentioning
confidence: 99%
“…Response eQTL mapping studies have demonstrated that genetic variation can modulate gene regulatory responses to environmental perturbations, such that the regulatory potential of a variant is unveiled only within a specific environmental context. Response QTL mapping studies not only uncovered context-specific functional genetic variants, but also uncovered the importance of personalized genomic characterizations in the study of environmental risk for human health (e.g., Barreiro et al, 2012;Knowles et al, 2017Knowles et al, , 2018Mangravite et al, 2013;Maranville et al, 2011;Moyerbrailean et al, 2016;Nedelec et al, 2016;Taylor et al, 2018). Overall, our understanding of the role of genetic variation in modulating the RNA processing response to environmental perturbations is still quite limited.…”
Section: Genetic Regulation Of Rna Processingmentioning
confidence: 99%
“…Despite being a conserved, basic cellular function, the ER stress response is subject to inter-individual variation in Drosophila, mouse, and humans [6][7][8][9]. It is only recently that we are beginning to appreciate the impact of genetic variation on the ER stress response.…”
Section: Introductionmentioning
confidence: 99%
“…It is only recently that we are beginning to appreciate the impact of genetic variation on the ER stress response. In Drosophila, we used natural genetic variation to demonstrate that susceptibility to ER stress is highly variable across strains and is associated with SNPs in both canonical and novel ER stress genes [6,7]. We also used mouse embryonic fibroblasts (MEFs) from inbred mouse strains to uncover a complex genetic architecture underlying the variable transcriptional response to ER stress among different genetic backgrounds [8].…”
Section: Introductionmentioning
confidence: 99%